Timor-Leste: representações dos estudantes Timorenses, no Brasil, sobre o Estado do Timor-Leste - Soares, Silvério dos Santos (2009)
The cultural identities in post-conflict countries where a constant layer of a process among all ethnic groups within the country to reaffirm its position in the formation of the nation. The identities of an ethnic group in the post-conflict always buy some proportions increasing through nuances in contemporary fields such as subject in the multiple representations of post-conflict. This dissertation is to address these propellers proactive in ethnic groups that represent the identities of ethnic groups in East Timor after independence in twenty of May two thousand and two. To cut this research, the subjects who were involved in this interview are the entities Timorese living in Brazil for the training process of the study in two Federal Universities in Brazil: Universidade Federal do Ceará (UFC) and Universidade Federal de Goiânia (UFG). In this sense, the goal is to draw a parallel between the Timorese authorities, of different ethnic groups that exist in the country that make the events of ethnic conflict in the country involving several entities of the ethnic groups after independence.